PODCAST-BASED LEARNING: EVALUATING THE SUCCESS OF LEARNING MEDIA DEVELOPMENT IN VOCATIONAL EDUCATION - Murtinugraha, R Eka; Arifah, Shilmi; Saleh, Rosmawita; Arthur, Riyan; Ostiyani, Nindya Reza (JURNAL EDUSCIENCE, 2025)
Purpose – This study evaluates the success of developing podcast-based learning media in Vocational Education Management courses in higher education. The background of this study is the need for innovation in learning media responsive to the development of digital technology, especially in supporting vocational learning that emphasizes practical and applied skills.Methodology – This study uses a quantitative approach with a survey design and an explanatory and correlational approach through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The sampling technique was randomly conducted on 168 students from five Building Engineering Education Study Program classes who had taken the course. The research instrument covers six variables: content, technical aspects, learning design, involvement and motivation, implementation and benefits, and perceived usefulness.Findings – The results showed that all indicators met convergent validity with an AVE value above 0.847 and high consistent reliability (CR> 0.95). The six aspects of the study contributed an influence of 87.10%, and the five measurement variables contributed 50.40%. Hypothesis H-DIR5 (IBA→PU) obtained a value of β = 0.213, T-statistic = 2.847 and ρ-value = 0.005. Based on this, the value of the technical aspect, implementation aspects, and benefits has a positive influence, which means that the more the two aspects increase, the more the perceived usefulness of media development increases.Significance – This study provides an empirical evaluation model for the effectiveness of podcast-based learning media in vocational education. These findings can be the basis for developing digital learning strategies that are more effective, interactive, and relevant to students' needs and the demands of the world of work in the digital era. In addition, this study's results can enrich the literature on applying the PLS-SEM model in evaluating technology-based learning media in higher education environments.